Advancing the Relationship between Critical Cataloging and Critical Race Theory. Issue 6 (3rd October 2022) - Snow, Karen; Dunbar, Anthony W.
Abstract: Critical race theory (CRT) is a framework that evolved from critical legal studies of the 1970s but has only recently been the target of intense scrutiny in education and politics. This article aims to describe CRT and how it can frame issues within cataloging and classification standards and practice. CRT tenets permanence of racism, whiteness as property, the critique of liberalism, intersectionality, counter-storytelling, and interest convergence are explored in the context of cataloging and classification work. Concepts of "authority" and "justice" are also examined. CRT can provide valuable evidence for critical cataloging efforts to make cataloging more diverse, equitable, and inclusive.